A Quantitative Test between Formalin Fresh and Boiled Fish at the Fish Market in Tulungagung - Setyowati, Lilis; Purwanto, Edi; Ningtyas, Nurmala Agustin (University of Muhammadiyah Malang, 2020)
Introduction: Fish is one of the sources of animal protein that many people look for because it is readily available and affordable. Nowadays, found in many traditional markets of traders, fish managers use formalin to preserve their wares. Objective: The purpose of this study was to determine differences in levels of boiled and fresh fish in TPI Tulungagung. Design quantitative analytic research studies cross-sectional. Quantitative formalin test with Formalin Kit returns UV-Vis spectrophotometer in the Biomedical Laboratory FK UMM, and Mann-Whitney test. The study population of fresh and boiled fish taken from 3 TPI in Tulungagung. The sampling technique was random sampling, each with four samples. Result: The results showed that the average value of formalin in boiled fish was 1.63 mg / â„“ and fresh 4.54 mg / â„“. There was a significant difference in formalin levels in boiled fish and fresh fish (p) <0.001. The samples from TPI Tulungagung contaminated formalin. However, the content of formalin in fresh fish is higher than boiled fish. It is very high from the BPOM standard. Discussion: The public is more concerned with the abuses committed, especially the use of formalin in circulation.